The Role of Gastronomy as a Cultural and Touristic Identity in Quito’s Historic Center - Quezada-Sarmiento, Pablo Alejandro; Chango-Cañaveral, Patricia Marisol (Journal of Posthumanism, 2025)
The research approached the gastronomy of the historic center of Quito city as a cultural reference of the capital since the gastronomic field is one of the motivations of confluence to various places of both foreign and national tourists. The historic center of Quito city is one of the most visited destinations in Ecuador it is considered the best preserved in the region and its culinary heritage is also one of the main motivations for your visit. This study reveals the main characteristics and how gastronomic tourism has been developed in the center of the city and how it is immersed with various cultural, historical elements and factors, of ancestral knowledge and flavors, it will need a diversification in the tourist market and finally in the gastronomic offer, through a bibliographic review in various search platforms, a compilation of several authors is made to reach the conclusion that Quito, being a Metropolitan District, has a variety of products that enrich and enhance its gastronomy, positioning it as a cultural reference within the capital..